Cold pool propagation and cold pool-land surface interactions - Falk, Nicholas Michael, author; van den Heever, Susan C., advisor; Grant, Leah D., advisor; Bell, Michael M., committee member; Schumacher, Russ S., committee member; Venayagamoorthy, Subhas K., committee member (Colorado State University. Libraries, 2025)
Convective cold pools are important components of the Earth system as they influence processes such as deep convective initiation, storm longevity and intensity, surface energy fluxes, and aerosol transport. The overarching goal of the research outlined in this dissertation is to investigate the propagation characteristics of cold pools, as well as the interactions between cold pools and the land surface. The three studies comprising this dissertation use field campaign observations and high-resolution numerical simulations to investigate these cold pool processes. The first study evaluates a popular density current propagation speed equation using a large, novel set of radiosonde and dropsonde observations. First, data from pairs of sondes launched inside and outside of cold pools, along with the theoretical density current propagation speed equation, are used to calculate sonde-based propagation speeds. Second, radar/satellite- based propagation speeds are calculated by manually tracking the propagation of cold pools and correcting for advection due to the background wind. Comparisons of the propagation speeds calculated in these different ways demonstrate that sonde-based and radar- based propagation speeds are strongly correlated for US High Plains cold pools, suggesting the density current propagation speed equation is appropriate for use in midlatitude continental environments. Sonde-based propagation speeds are largely insensitive to how cold pool depth is defined, since the preponderance of negative buoyancy is near the surface in cold pools. Sonde-based propagation speeds can vary by ~300% based on where and when the sondes were launched, suggesting sub-mesoscale variability could have a major influence on cold pool propagation. The impacts of topographic slope on daytime haboob propagation speeds and dust lofting are examined in the second study comprising this dissertation, along with how these impacts are modulated by surface roughness length. A suite of 40 idealized, large-eddy simulations are conducted with varied linear topographic slopes and surface roughness lengths. It is found that on flat ground, greater surface roughness increases drag on haboobs and causes haboobs to dissipate faster, thereby decreasing both haboob propagation speeds and associated dust lofting. As the topographic slope is increased, an upslope anabatic wind forms which causes downslope haboob propagation speeds to decrease and upslope haboob propagation speeds to be mostly unchanged. Anabatic winds act to loft dust as well, leading to increased masses of dust being lofted jointly by the haboob and anabatic wind as topographic slopes are increased. The third study investigates the individual and synergistic impacts of cold pools and land surface heterogeneity on convection initiation. Idealized large eddy simulations of deep convection over the Amazon rainforest are conducted testing realistic and homogenized vegetation, along with realistic and eliminated cold pools. Convection initiation is more frequent over forested than deforested areas due to more favorable thermodynamics. Heterogeneous vegetation aggregates storm initiation locations compared with homogeneous vegetation. Over heterogeneous vegetation, cold pools propagate into deforested regions, thereby initiating storms and disaggregating storm initiation locations. Convection initiation locations are randomly distributed over homogeneous vegetation, with or without cold pools, demonstrating that cold pools have minimal impacts on convection initiation locations over homogeneous vegetation. The findings of this dissertation research shed new light on fundamental cold pool processes and should be helpful for improving the representation of cold pools in forecast and climate models. Several avenues for future research are discussed.